دراسة مقاصدية في تعددية قانون الإرث (دراسة حالة منطقة تنغاران): A Maqasid al-Sharia Perspective on Legal Pluralism in Inheritance Law (A Study in Tengaran District) - Khodijah Khodijah; Ahmad Husaini (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2026)
This study analyzes inheritance distribution practices within the context of legal pluralism in Tengaran District, Semarang Regency, and examines their conformity with the principles of Maqasid Syariah. The study aims to enrich contemporary legal discourse on inheritance among Muslim communities living under systems of legal pluralism. Employing a qualitative approach through interviews, questionnaires, and field observation across six villages (Patemon, Butuh, Karangduren, Sugihan, Klero, and Tengaran). The primary data were processed through narrative analysis methodology. The findings reveal that formal legal mechanisms, such as the Compilation of Islamic Law (the official regulations on Islamic family law in Indonesia), are rarely invoked as explicit references in inheritance distribution. Instead, the community prioritizes family-based consensual agreements (ishlah) rooted in local harmony and contextual justice. Local authorities maintain a limited role, primarily providing declaratory administrative services to document heirship. When evaluated against the five pillars of Maqasid al-Shari'ah, these practices only partially fulfill the shari'ah objectives. This partial fulfillment arises because these consensual agreements are dictated more by sociocultural norms and local customs than by a formal jurisprudential understanding of Islamic law. The study therefore recommends strengthening Islamic legal literacy within the community through the active involvement of religious figures in deliberation processes, alongside a reinforcement of the local government's role in overseeing such consultations, so that any agreement reached may stand on a foundation of sound and informed legal consciousness.